Increasing science process skills using inquiry learning model - Ifa Aulia; Astrid Sri Wahyuni Sumah; Marlina Ummas Genisa (Jurnal Pijar Mipa, 2023)
The teacher is a facilitator in determining learning objectives to improve the learning process, and students can actively conduct discussions andseek their own experiences. However, teachers must still implement learning models and science process skills in biology lessons so that learning becomes monotonous. Before carrying out science process skills in learning at school, the teacher must first know the profile of students' science process skills (SPS) so that they can support science process skills following the conditions of students. This study aimed to improve students' science process skills by applying inquiry learning models to biotechnology material in class XII IPA 1 MA Aisyiyah Palembang. The research method used was classroom action research by applying an inquiry learning model consisting of 2 cycles with six meetings, with three in each cycle. The subjects of this study were students of class XII IPA 1 MA Aisyiyah Palembang, with a total of 18 students. The results of the study found an increase in students' SPS scores. Cycle 1 basic skills (89.96%) increased in cycle 2 (96.29%), cycle one process skills (90.43%) increased in cycle 2 (94.13%), and investigative skills in cycle 1 (46.29%) also increased in cycle 2 (86.10%). The findings prove that applying the inquiry learning model can increase students' science process skills.